Effect of the combination of materials for inclusion at different pressures on the mobility of artificial teeth during prosthetic processing - Jaramillo Ruiz, Letty Cecibel (2018)
Objective: Compare the artificial teeth changes position in the maxillary total prosthesis at the time of pressing, by measuring at certain pre-determined reference points, under different types of pressure force of 800, 1 000 and 1 250 kg, using Type III gypsum (Whip Mix, USA®) and condensation silicone (Zhermack, Italy) as inclusion materials. Methods: 36 superior prostheses obtained from a plaster model of a single total edentulous patient were fabricated. The copies were randomly divided into 6 groups each with 6 repetitions, considering the involved variables, materials and evaluiated strength after press and process of being transformed in acrylic. The difference between the reference points was established by Autocad (21.2 version Autodesk, Spain). Results: significant difference was detected between silicone and gypsum at 1 000 force at 1% of significance level. Conclusions: Standing out more stability in terms of movement when used silicone as material for inclusion, with better results when using under 1 000 kg pressure force, independent of the pressure tested in all samples there was movement in the artificial teeth original position